Comprehensive Physiology 1983
DOI: 10.1002/cphy.cp100115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ca2+Transport by Sarcoplasmic Reticulum

Abstract: The sections in this article are: Structure of Sarcoplasmic Reticulum and Transverse Tubules Structure of Plasmalemma and T Tubules Sarcoplasmic Reticulum Junction Between T Tubules and SR Mechanism of Excitation‐Contraction Coupling Isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 616 publications
3
19
0
Order By: Relevance
“…It is also seen that the extrinsic protein, calsequestrin (a usual component of sarcoplasmic reticulum vesicles) is degraded by trypsin in the absence of Ca 2+ and vanadate, but not in the presence of either one of these ions. This indicates that the membrane is destabilized by digestion in absence of CaZ+-ATPase ligands since calsequestrin is located at the interior surface of the sarcoplasmic reticulum vesicle [30,40]. In accordance with this interpretation we found that ATPdriven net uptake of Ca 2+ into the vesicles disappears after tryptic digestion in absence of Ca 2+, whereas CaZ+-ATPase activity is stimulated (Table 1).…”
Section: Methodssupporting
confidence: 67%
“…It is also seen that the extrinsic protein, calsequestrin (a usual component of sarcoplasmic reticulum vesicles) is degraded by trypsin in the absence of Ca 2+ and vanadate, but not in the presence of either one of these ions. This indicates that the membrane is destabilized by digestion in absence of CaZ+-ATPase ligands since calsequestrin is located at the interior surface of the sarcoplasmic reticulum vesicle [30,40]. In accordance with this interpretation we found that ATPdriven net uptake of Ca 2+ into the vesicles disappears after tryptic digestion in absence of Ca 2+, whereas CaZ+-ATPase activity is stimulated (Table 1).…”
Section: Methodssupporting
confidence: 67%
“…The absence of detectable cardiolipin and cholesterol shows that there was little mitochondrial lipid. Skeletal muscle sarcoplasmic reticulum (Martonosi & Beeler, 1983) has higher propor- …”
Section: Phospholipid Composition Of Z-disc Preparationsmentioning
confidence: 99%
“…Regulatory proteins include phospholamban, which is thought to impart slow kinetic properties to the SERCA2 pump in slow fibers (23,28), and sarcolipin, a protein found in fast fibers that appears to confer fast pump kinetics to the SERCA1 isoform (34). In addition, fast fibers contain higher total amounts of SR (as measured by SR membrane volume percentage) and total SERCA protein (13,32). Thus different fiber types have both qualitative and quantitative differences in SR properties, each of which may contribute to the greater fatigability of fast fibers (15,16,53).…”
mentioning
confidence: 99%